Edwards syndrome with a novel karyotype - Patra, S; Garg, A; Krishnamurthy, S; Aneja, S (Bangladesh Journal of Medical Science, 2011)
Edward’s syndrome was first described as a clinical entity in 1960 as a disorder of trisomy 18 (47 XX/XY; + 18) in babies with particular pattern of malformations. The Karyotype found in our case was (47 XX + 18 add (22) (p13) which has not been published so far in the literature. The less common findings noted in the baby were rocker bottom feet, syndactyly of 2nd and 3rd toes, microcephaly and corneal opacities. Though we didn’t find any significant association between phenotypic ranges with genotypic variation in literature, but further research is needed for it. We are reporting this case as the genotype is found to be novel. Keywords: Edward’s syndrome, karyotype, neonate. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8368 BJMS 2011; 10(3): 211-212